1997
DOI: 10.1007/s004390050576
|View full text |Cite
|
Sign up to set email alerts
|

A human gene similar to Drosophila melanogaster peanut maps to the DiGeorge syndrome region of 22q11

Abstract: A Drosophila-related expressed sequence tag (DRES) with sequence similarity to the peanut gene has previously been localized to human chromosome 22q11. We have isolated the cDNA corresponding to this DRES and show that it is a novel member of the family of septin genes, which encode proteins with GTPase activity thought to interact during cytokinesis. The predicted protein has P-loop nucleotide binding and GTPase motifs. The gene, which we call PNUTL1, maps to the region of 22q11.2 frequently deleted in DiGeor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 40 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…This is surprising given the number of linkages of CDCrel-1 to disease and neuronal function. First, CDCrel-1 had been identified within the locus that is commonly deleted in patients with DiGeorge syndrome (28). In these individuals, haploinsuffi- FIG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is surprising given the number of linkages of CDCrel-1 to disease and neuronal function. First, CDCrel-1 had been identified within the locus that is commonly deleted in patients with DiGeorge syndrome (28). In these individuals, haploinsuffi- FIG.…”
Section: Discussionmentioning
confidence: 99%
“…In the first study, CDCrel-1 was found as the upstream part of a fusion transcript containing the ␤-subunit of the glycoprotein 1b platelet receptor (43) due to its nonconsensus polyadenylation sequence. As well, CDCrel-1 was identified as a gene within the segment of chromosome 22q11.2 that is commonly deleted in velo-cardiofacial and DiGeorge syndromes in humans (28). The latter is a complex congenital disorder including parathyroid and thymic hypoplasia as well as defects of the heart, which results, in part, in impaired migration of neural crest cells into the pharyngeal arches and pouches.…”
mentioning
confidence: 99%
“…However, this choice would prove later to be less than perfect, because we observed the highest levels of CDCrel-1 mRNA in organs and cells no longer undergoing active cell division, namely brain, heart, and megakaryocytes (6). CDCrel-1 also has been referred to as PNUT-like based on its similarity to the well characterized Drosophila septin (7,8).…”
mentioning
confidence: 99%
“…To date, nine septin genes have been identified in mammalian genomes: Diff6 (Nottenburg et al, 1990), H5 (Kato, 1990), CDC10 (Nakatsuru et al, 1994), Nedd5/KIAA0158 (Kumar et al, 1992;Nagase et al, 1995;Kinoshita et al, 1997), CDCrel-1/PNUTL1 (McKie et al, 1997;Zieger et al, 1997), KIAA0128/Septin6 (Nagase et al, 1995), KIAA0202 (Nagase et al,1996), E-septin/KIAA0991 (Fung and Scheller, 1999;Nagase et al, 1999), and G-septin (Xue et al, 2000). Nedd5, CDC10, Diff6, and Septin6 colocalize near the contractile ring during cytokinesis in human cells, and microinjection of anti-Nedd5 antibodies interferes with cytokinesis of cultured cells, suggesting that septins play important roles in cytokinesis in mammalian cells (Kinoshita et al, 1997;unpublished observations).…”
mentioning
confidence: 99%